Reviewing Religious Pluralism Through A Qur’anic Approach: The Relevance of Hamka’s Tafsir Al-Azhar in Indonesia and Malaysia - Harda Armayanto,; Suntoro, Adib Fattah; Achmad Reza Hutama Al Faruqi,; Maria Ulfa,; Amir Sahidin, (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
This research examines the Qur’anic approach to interreligious relations through an in-depth analysis of Hamka’s Tafsir al-Azhar. The relevance of this study becomes evident considering that religious diversity often triggers conflict and intolerance, as seen in Indonesia and Malaysia. On the other hand, Western approaches, such as religious pluralism, frequently spark controversy and rejection among religious adherents because they are perceived to blur theological boundaries between religions and contradict religious doctrines. Therefore, an approach grounded in religion is more relevant for fostering constructive interreligious relations. The research methodology is qualitative, involving a literature review of Tafsir al-Azhar and related writings, along with content analysis. The results of this investigation imply that religious pluralism is unsuitable as an approach for building interreligious relations in Indonesia and Malaysia, given the doctrinal conflicts it poses with the beliefs of various religions. In contrast, a religiously grounded approach, particularly as reflected in the Holy Qur’an through Hamka's Tafsir al-Azhar, is more relevant for creating harmonious interreligious relationships. This approach incorporates key Qur'anic concepts, such as tasāmuḥ/samāḥah (tolerance), ḥuriyyah (freedom), salām (peace), ‘adālah (justice), iḥsān (benevolence), and wasatiyah (moderation).